O Regime Disciplinar Diferenciado em face das Teorias Justificadoras das Penas - Desgualdo, Antonio Carlos de Aguiar (2007)
The present work, is a requirement for the Pontifical Catholic University os Sao Paulo Masters Degree, and its subject tell us about the Regime Disciplinar Diferenciado , created by the Resolution 10.792 (December, 1st, 2003), wich has modified the Brazilian Criminal Execution Law. This research was developed by foreign and national legislation and doctrine, and also by National Court decisions and jurisprudence. This work clains to identify the aim aplication of the Regime Disciplinar Diferenciado , wich is, as we know, a development of the punishment. This research brings a superficial analysis of all punishment justifying theories. The conclusion of the objectives brought by the Regime Disciplinar Diferenciado - System it is a personal annulment, suffered by the punished, also brought by his isolation. At this moment, it is characterized the Special Negative Preventive Theory, wich is unconstitutional and reaches the Principal of the Human Rights